2011
DOI: 10.1681/asn.2009091005
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Visual Evaluation of Fibrosis in Renal Biopsies

Abstract: Interstitial fibrosis is an outcome measure of increasing importance in clinical trials of both renal transplantation and native disease, but data on the comparative advantages of fibrosis measurement methods are limited. We compared four morphometric techniques and contrasted these with two visual fibrosis-scoring methods on trichrome-stained slides. Two morphometric methods included whole-slide digital images: collagen III immunohistochemistry and a new technique using trichrome and periodic acid-Schiff subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
211
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(220 citation statements)
references
References 42 publications
(57 reference statements)
2
211
1
6
Order By: Relevance
“…At least one study offers reassurance that this is not the case (361). Protocol biopsies of the renal allograft may also provide important sequential information on renal fibrosis, in particular when evaluated quantitatively (362)(363)(364). Thus, biopsies obtained from renal transplant recipients at day 0 and month 3 and 12 showed a rapid progression of IF scores from 19% to 27% at month 3 and 32% at month 12 (363).…”
Section: Diagnosis Of Renal Fibrosismentioning
confidence: 99%
“…At least one study offers reassurance that this is not the case (361). Protocol biopsies of the renal allograft may also provide important sequential information on renal fibrosis, in particular when evaluated quantitatively (362)(363)(364). Thus, biopsies obtained from renal transplant recipients at day 0 and month 3 and 12 showed a rapid progression of IF scores from 19% to 27% at month 3 and 32% at month 12 (363).…”
Section: Diagnosis Of Renal Fibrosismentioning
confidence: 99%
“…In renal allograft studies, the extent of interstitial fibrosis is used to prognosticate the life of an allograft (Farris et al 2011). Though it is not clear whether a causal relationship between fibrosis and chronic renal function loss exists (Mack and Yanagita 2015), a reciprocal correlation lies between kidney function and interstitial fibrosis extent (Farris et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In renal allograft studies, the extent of interstitial fibrosis is used to prognosticate the life of an allograft (Farris et al 2011). Though it is not clear whether a causal relationship between fibrosis and chronic renal function loss exists (Mack and Yanagita 2015), a reciprocal correlation lies between kidney function and interstitial fibrosis extent (Farris et al 2011). In the past decade, the supposition that fibrosis is irreversible was challenged by a study that showed, in patients with diabetic nephropathy, the progression of chronic lesions could be repaired on pancreas transplantation (Fioretto et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Those techniques are recommended and widely applied in the clinical setting. 18 Evaluation of renal function with estimated GFR are very important for the diagnosis and treatment of patients with CKD. Fomula Cockcroft -Gault and modification of diet renal disease formula (MDRD) are most commonly used with some limitations.…”
mentioning
confidence: 99%